Networking and growth of young technology-intensive ventures in China - Zhao, Liming; Aram, John D. (Journal of Business Venturing, 1995)
More often than not, new ventures lack established products, known technologies, longstanding customer relations, experienced managerial teams, sufficient capital, and strong reputations. Almost by definition, small, new firms lack the resources of many larger, established firms. The task of an infant firm, and a measure of its success, is to make a transition from being resource weak to being resource strong. How can resources that are critical for profitable growth be acquired for the resource weak new venture? Researchers have found that entrepreneurs can gain access to valuable resources and they can seek to achieve competitive advantage through “networking activities.” Forming and utilizing available relationships with external organizations can allow entrepreneurs to build credibility, gain advice, financing, and customer access, build a positive image and obtain resources at below-market prices, and obtain channel access, information, and innovations. Business relationships with other organizations allow an entrepreneur to achieve desired business results through “asset parsimony.” A favorable view toward networking for new ventures leaves a number of unanswered questions, however. Relevant research questions might include, who should the entrepreneur seek as a business partner? Are all inter-organizational relationships equal, or are some types more valuable to new ventures than other relationships? Do firms relying on high levels of networking activities actually outperform firms that less actively seek resources through external organizational relationships? The present study provides a specific understanding of the concept of networking for entrepreneurs. We propose that networking can be understood in terms of “range,” the number of external relationships to obtain resources, and of “intensity,” the frequency of contact of and amount of resource obtained from these relationships. This research project evaluates the range and intensity of networking among high-growth and low-growth entrepreneurial ventures. Extensive interviewing with managers of six young technology-oriented firms in the People's Republic of China (PRC) affirmed the importance of entrepreneurial networking. Managers in the three high-growth firms reported greater range and intensity of business networking than did managers of three low-growth firms, matched by industry and age. Moreover, the relationship between networking activities and growth transcended the stage of firm development. Where networking range and intensity are deemed important in the growth process, new venture success may call for entrepreneurs to reach out deliberately to external organizations to capture needed resources. To a certain extent, such networking activities run counter to important entrepreneurial motivations of independence and autonomy. The concept of networking, and the results of this study, imply that entrepreneurs need to combine the spirit of independence with the reality of resource dependence, and they need to balance personal autonomy with strategic business relationships. This study also contributes to the understanding of entrepreneurship in our increasingly global economy, particularly in the PRC. Business relationships between the United States and the PRC have been expanding rapidly in the last decade. Many foreign businesses seek license agreements, joint venture partners, equity participation, or channel relationships with young ventures in that country. Do the same rules of networking apply in the PRC as the literature suggests apply in the United States? New ventures in this study were found to engage in processes of networking activities consistent with those in the West. Although networking activities may have different cultural roots, firm success appeared influenced by the same principles of networking.